Negative pole piece and sodium ion secondary battery comprising same
By adjusting the content of F and C elements in the negative electrode of the sodium ion battery, the problems of difficulty in starting up in a low-temperature environment and high DC internal resistance are solved, and better low-temperature cold start performance and overall application performance are achieved.
Patent Information
- Application Number
- CN202411916820.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional sodium ion batteries have problems such as low platform voltage, difficulty in starting the vehicle in a low temperature environment, high DC internal resistance, large DC internal resistance growth after circulation and storage, and gas production after high temperature storage, which limits its application performance.
A negative electrode sheet is provided, and the negative electrode active layer contains F elements and C elements, the mass content of F elements is 0 wt% < Fwt% ≤ 7.6 wt%, and the mass content ratio of F elements to C elements is 0% < Fwt%/Cwt% × 100% ≤ 8.44%. By adjusting the content of F and C elements, the negative electrode sheet improves the wetting and adhesion of the electrolyte, reduces the film formation potential and time of the SEI film, improves the transmission efficiency of sodium ions, and improves the low-temperature cold start performance of the battery.
By optimizing the F element and C element content of the negative electrode sheet, the low-temperature cold start performance of the sodium ion battery is improved, the electrochemical polarization and concentration polarization are reduced, and the overall application performance of the battery is improved.
Smart Images

Figure CN119725381A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a negative electrode plate and a sodium ion secondary battery containing the same. Background Art
[0002] With the acceleration of global energy transformation, especially the growing demand for clean and efficient energy storage solutions, lithium-ion batteries have become the first choice for new energy storage technology due to their high energy density, long cycle life and fast charging capabilities. However, limited by the shortage of raw materials for lithium-ion batteries and their rapid price increases, sodium-ion batteries are widely used in energy storage, two-wheel vehicles, start-stop and other directions due to their abundant raw materials and low prices. However, traditional sodium-ion batteries usually have problems such as low platform voltage, difficulty in starting the vehicle in low temperature environments, high DCR, large DCR growth after cycling and storage, and gas production after high-temperature storage, which limits the promotion and application of sodium-ion batteries. Summary of the invention
[0003] The present application provides a negative electrode plate, which aims to improve to a certain extent the problem of poor film forming performance of the negative electrode end of a sodium ion battery, thereby affecting the low-temperature cold start performance of the battery.
[0004] The present application also provides a sodium ion secondary battery comprising the above-mentioned negative electrode plate.
[0005] In a first aspect, the present application provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector;
[0006] The negative electrode active layer contains F element and C element, wherein:
[0007] The mass content of the F element based on the total amount of the negative electrode active layer wt% Satisfies: 0wt%<F wt% ≤7.6wt%;
[0008] The mass content of F element F wt% and the mass content of the C element C wt% Satisfy the following relationship: 0%<F wt% / C wt% ×100%≤8.44%.
[0009] In a second aspect, the present application provides a sodium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet; the negative electrode sheet is the negative electrode sheet described in the first aspect above.
[0010] The technical solution of this application has the following advantages:
[0011] The negative electrode sheet provided in the present application is provided by adjusting the mass content of F element in the negative electrode active layer. wt% Satisfy: 0wt%<Fwt%≤7.6wt%, and adjust the mass content of the F element F wt% and the mass content of the C element C wt% The following relationship is satisfied: 0%<Fwt% / Cwt%×100%≤8.44%. In the research on the negative electrode sheet described in the present application, it is found that when the F element and the C element satisfy the aforementioned relationship, they can have good wettability with the electrolyte, and at the same time have relatively stable adhesion, and conduct ions and transfer electrons, reduce the film formation potential of the SEI film, shorten the film formation time of the SEI film, improve the stability of the SEI film, improve the transmission efficiency of sodium ions and electrons, reduce the electrochemical polarization and concentration polarization during the charge and discharge process, improve the low-temperature cold start performance of the battery, and effectively guarantee the application performance of the sodium ion battery.
[0012] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0014] Figure 1 is the SEM image of the pole piece in Example 1 and Comparative Example 1;
[0015] Figure 2 1 is the element distribution spectrum of the electrode of Example 1 and Comparative Example 1;
[0016] Figure 3 DQ / DV curves of the first charge of the sodium ion battery in Application Example 1 and Comparative Application Example 1;
[0017] Figure 4 ICA curves of single charge and discharge of the sodium ion battery in Application Example 1 and Comparative Application Example 1;
[0018] Figure 5 This is the dQ / dV cycle curve of the sodium ion battery cycle process in Application Example 1. DETAILED DESCRIPTION
[0019] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0020] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0021] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0022] The present application provides a negative electrode plate and a sodium ion secondary battery, which can to a certain extent improve the problems of sodium ion batteries, such as low platform voltage, difficulty in starting the vehicle in a low temperature environment, high DC internal resistance, large increase in DC internal resistance after cycling and storage, and gas generation after high-temperature storage.
[0023] In a first aspect, the negative electrode sheet provided by the present application comprises a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector;
[0024] The negative electrode active layer contains F element and C element, wherein:
[0025] The mass content of the F element based on the total amount of the negative electrode active layer wt% Satisfies: 0wt%<F wt% ≤7.6wt%;
[0026] The mass content of F element F wt% and the mass content of the C element C wt% Satisfy the following relationship: 0%<F wt% / C wt% ×100%≤8.44%.
[0027] It is understood by those skilled in the art that conventional sodium ion batteries generally have problems such as low platform voltage, difficulty in starting the vehicle in low temperature environment, high DCR, large DCR growth after cycling and storage, and gas generation after high temperature storage, which limits their performance in certain application scenarios. In order to solve the above problems, the negative electrode sheet provided in this application is modified by adjusting the mass content of F element in its negative electrode active layer. wt% Satisfies: 0wt%<F wt% ≤7.6wt%, and adjust the mass content of F element in the negative electrode plate wt% and Cwt% Element content meets: 0%<F wt% / C wt% ×100%≤8.44%. In the research on the negative electrode sheet described in the present application, it was found that when the mass contents of the F element and the C element in the negative electrode sheet satisfy the above relationship, it can have good wettability with the electrolyte, and by adjusting the matching between the mass content of the F element and the mass content of the C element, the adhesion and film-forming properties of the entire negative electrode active layer are improved, and ions are conducted and electrons are transferred, the negative end film formation is more stable, the stability of the negative end is effectively guaranteed, the low-temperature cold start performance of the battery is further improved, and the application performance of the sodium ion battery is effectively guaranteed. It should be noted that when the ratio of the mass content of the F element and the C element in the negative electrode plate is too large, it is easy to cause the local surface capacity of the plate to be low, resulting in local sodium precipitation on the surface of the plate, increasing the battery impedance and electrochemical polarization, resulting in a decrease in the platform voltage, and a decrease in cold start performance; when the ratio of the mass content of the F element and the C element in the negative electrode plate is too small, it is easy to cause the electrolyte wettability of the plate to deteriorate, the adhesion between the plate and the current collector to deteriorate, resulting in an increase in electronic impedance, a decrease in the platform voltage, and a decrease in cold start performance.
[0028] When the F element and the C element of the negative electrode plate described in the present application satisfy the following conditions: 0wt%<Fwt%≤7.6wt% and 0%<Fwt% / Cwt%×100%≤8.44%, the plate can have good wettability with the electrolyte, and at the same time have relatively stable adhesion, and can conduct ions and transfer electrons. The film formation at the negative end is more stable, and the charge and discharge process reduces the electrochemical polarization and concentration polarization, thereby improving the low-temperature cold start performance of the battery and effectively ensuring the application performance of the sodium ion battery.
[0029] In an optional embodiment, the negative electrode active layer includes a conductive agent, and the distribution content of the conductive agent on the surface of the negative electrode active layer is 20%-35%. It should be noted here that the distribution content of the conductive agent means the area ratio of the conductive agent on the surface of the negative electrode active layer. As an exemplary embodiment, the step-by-step content of the conductive agent is adjusted to 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, etc., or within the range of any two of the above values. In the negative electrode sheet described in the present application, when the distribution content of the conductive agent on the surface of the active layer is adjusted to meet this range, the content relationship between F and carbon elements can be coordinated to promote the formation of the SEI film and the uniformity of the film formation, reduce the impedance of electrons and ions, and improve the cold start performance of the battery.
[0030] In an optional embodiment, the conductive agent includes at least one of carbon nanotubes, carbon black, conductive graphite, graphene or carbon fiber.
[0031] In some preferred embodiments, the conductive agent comprises at least carbon nanotubes and / or carbon black;
[0032] In some preferred embodiments, the conductive agent includes a mixture of carbon nanotubes and / or carbon black, and at least one selected from the conductive graphite, graphene or carbon fiber.
[0033] In an optional embodiment, the conductive agent includes carbon nanotubes. In the negative electrode active layer, the mass content of the F element is wt% The aspect ratio d of the carbon nanotube satisfies the following relationship: 0<F wt% ×d≤380, and more preferably 1≤F wt% ×d≤80. As an exemplary embodiment, the F wt% The value of ×d is 1, 3, 5, 50, 80, 100, 150, 200, 250, 300, 350, 380, etc., or is within the range of any two of the above values. wt% ×d≤380; the carbon tubes in the negative electrode active layer can be adjusted to have better dispersion, improve the uniformity of the electrode conductivity, and take into account the electrolyte wettability of the electrode, which can reduce the electrode impedance and polarization, which is beneficial to the deintercalation of sodium ions, and improve the low-temperature discharge performance and the low-temperature cold start performance of the battery, with a higher first efficiency; and in the temperature range of -30°C to 60°C, above the average voltage at the corresponding temperature, the amount of sodium ion deintercalation in the negative electrode accounts for more than 53% of the total capacity.
[0034] In an optional embodiment, the aspect ratio d of the carbon nanotubes satisfies the following relationship: 300≤d≤5000, and preferably 400≤d≤2900; as an exemplary embodiment, the aspect ratio d of the carbon nanotubes can be adjusted to 300, 400, 800, 1000, 1500, 2000, 2500, 2900, 3000, 3500, 4000, 4500, 5000, etc., or within the range of any two of the above values. The appropriate aspect ratio of the carbon nanotubes helps to improve the dispersibility of the carbon nanotubes in the active layer, meet the conductive performance advantages of the conductive agent, and especially ensure better wetting performance between the negative electrode plate and the electrolyte.
[0035] In an optional embodiment, the diameter of the carbon nanotube is 5nm-15nm; as an exemplary embodiment, the diameter of the carbon nanotube can be adjusted to 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, etc., or within the range of any two of the above values. The appropriate diameter size of the carbon nanotube helps to meet its dispersion state in the negative electrode plate, helps to form a more stable negative electrode plate system, and reduces the DC internal resistance of the battery.
[0036] In an optional embodiment, the specific surface area of the carbon nanotubes is 150 m 2 / g-350m 2 / g; As an exemplary embodiment, the specific surface area of the carbon nanotubes can be adjusted to 150m 2 / g, 180m 2 / g, 200m 2 / g, 220m 2 / g, 250m 2 / g, 280m 2 / g、300m 2 / g, 320m 2 / g, 350m 2 / g, etc., or within the range of any two of the above values. The appropriate specific surface area of the carbon nanotubes effectively ensures the contact area with the outside world, makes it easier to form a uniform conductive path, and ensures the wetting and conductivity between the negative electrode plate and the electrolyte, thereby reducing the DC internal resistance of the battery.
[0037] In an optional embodiment, the conductive agent includes carbon black.
[0038] In an optional embodiment, the primary particle size of the carbon black is 18nm-35nm; as an exemplary embodiment, the primary particle size of the carbon black can be adjusted to 18nm, 20nm, 22nm, 25nm, 28nm, 30nm, 32nm, 35nm, etc., or within the range of any two of the above values. The primary particle size of the carbon black helps it form a more uniform conductive network, ensure the conductive performance advantage of the entire negative electrode plate, and reduce the DC internal resistance of the battery.
[0039] In an optional embodiment, the specific surface area of the carbon black is 120 m 2 / g-180m 2 / g; As an exemplary embodiment, the specific surface area of the carbon black can be adjusted to 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, etc., or within the range of any two of the above values. Similarly, the appropriate specific surface area of the carbon black effectively ensures its contact area with the outside world, makes it easier to form a uniform conductive path, and ensures the wetting and conductivity between the negative electrode plate and the electrolyte, thereby reducing the DC internal resistance of the battery.
[0040] In an optional embodiment, the oil absorption value of the carbon black is 150ml / 100g-180ml / 100g; as an exemplary embodiment, the oil absorption value of the carbon black can be adjusted to 150ml / 100g, 155ml / 100g, 160ml / 100g, 165ml / 100g, 170ml / 100g, 175ml / 100g, 180ml / 100g, etc., or within the range of any two of the above values. The carbon black is screened for a suitable oil absorption value, which improves the wettability of the electrode electrolyte and the stability of the SEI film, which is conducive to reducing polarization, reducing internal resistance, and improving the cold start performance of the battery.
[0041] In an optional embodiment, the conductive agent includes a mixture of carbon nanotubes and carbon black; preferably, the mass ratio of the carbon nanotubes and carbon black is 1:3-1:6. As an exemplary embodiment, the mass ratio of the carbon nanotubes and carbon black is adjusted to 1:3, 1:4, 1:5, 1:6, etc., or within the range formed by any two of the above values. The negative electrode plate described in the present application utilizes a mixed system of carbon nanotubes and carbon black as a conductive agent, and the ratio between the two is more optimally screened to be 1:3-1:6. The combination of carbon nanotubes and carbon black size and other properties is utilized to more effectively improve the conductive properties of the negative electrode plate, reduce the internal resistance of the battery, and enhance the cold start performance of the battery.
[0042] In an optional embodiment, the conductive agent further includes one or more mixtures of graphite, graphene, carbon fiber, etc., and the added amount of the above conventional conductive agent is preferably within the range acceptable in the art.
[0043] In an optional embodiment, the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes hard carbon.
[0044] In an optional embodiment, the hard carbon includes hard carbon with irregular angular structure. As an exemplary embodiment, hard carbon particles with smaller particle size and / or larger specific surface area can be selected to facilitate sodium ion insertion and extraction, thereby improving rate performance.
[0045] In an optional embodiment, the water content of the hard carbon is ≤300ppm. When this type of hard carbon material is used to prepare the negative electrode plate, the moisture is easily baked out, thereby ensuring the initial performance, high-temperature storage performance and cyclic gas production.
[0046] In an optional embodiment, the negative electrode active layer includes a binder, and the binder includes a fluorine-containing binder. The fluorine-containing binder known in the art can control the fluorine content of the entire negative electrode plate by adjusting its addition amount. wt% Meeting the requirements can not only ensure the regulation of the fluorine content in the entire negative electrode plate, but also has the advantage of easy availability of raw materials.
[0047] As an exemplary embodiment, the binder preferably uses PVDF. Since oily PVDF is used as the binder, it has good wettability with the electrolyte, is resistant to high voltage and oxidation, and is more stable. During the charge and discharge process, the negative electrode kinetics is improved, making it easier for sodium ions to shuttle, reducing electrochemical polarization and concentration polarization, and significantly improving the use of the battery under low-temperature cold start and low-temperature operating conditions. At the same time, the use of oily PVDF as a binder helps to ensure that the water content in the negative electrode plate is extremely small, which significantly improves the subsequent long-term cycle and storage performance.
[0048] In an optional embodiment, the negative electrode active layer includes a negative electrode active material, a binder and a conductive agent; wherein, based on a total amount of 100wt%, the mass ratio of the negative electrode active material, the binder and the conductive agent is 88wt%-96wt%: 0.34wt%-10wt%: 1-8wt%.
[0049] As an exemplary embodiment, the mass ratio of the negative electrode active material, the binder and the conductive agent can be adjusted to 88wt%:10wt%:2wt%, 91wt%:3.5wt%:5.5wt%, 92wt%:1wt%:5wt%, 93wt%:2wt%:5wt%, 94wt%:3wt%:3wt%, 95wt%:1wt%:4wt%, 96wt%:1wt%:3wt%, 91.66wt%:0.34wt%:8wt%, etc., or within the range of any two of the above values.
[0050] The negative electrode sheet of the present application, based on the regulation of the parameters of the entire negative electrode sheet, has at least one of the following features (a)-(e):
[0051] (a) The first efficiency of the negative electrode meets 85%-95%, and the first efficiency parameters of the negative electrode are conducive to improving the overall first efficiency performance of the battery cell;
[0052] (b) The electrode sheet surface resistance meets the requirements of 1mΩ-4mΩ, which helps to reduce the electrode sheet ohmic impedance, improve the conductivity of the electrode sheet and thus improve its cycle performance;
[0053] (c) The electrode resistivity meets the requirements of 0.001Ω·m-0.01Ω·m, which can reduce the electrode ohmic impedance, improve the conductivity of the electrode and thus improve its cycle performance;
[0054] (d) The average peeling force of the pole piece meets 0.24N-3.5N, which is conducive to binding particles, thereby reducing expansion, preventing peeling, improving the stability of the pole piece, and improving problems such as gas generation after high-temperature storage;
[0055] (e) The electrode porosity is 45%-55%, which is conducive to electrode wetting, ensuring the formation of ion channels and ensuring the low-temperature cold start performance of the negative electrode;
[0056] Preferably, the negative electrode plate also has at least one of the following features (f)-(i):
[0057] (f) The gram capacity of the negative electrode meets 280 mAh / g-330 mAh / g. The gram capacity data of the negative electrode is conducive to ensuring a certain energy density and ensuring the cycle and storage performance of the electrode sheet;
[0058] (g) The water content of the electrode should be 100ppm-400ppm after baking before liquid injection to avoid excessive gas generation during formation and subsequent charge and discharge processes, and to ensure the stability of the electrode and battery, especially the stability of low-temperature startup;
[0059] (h) The compaction density of the pole piece meets 0.8g / cm 3 -1.5g / cm 3 It helps to ensure that the electrode has high flexibility, while building ion and electron channels, which helps to improve the problems of large increase in DC internal resistance after circulation and storage, and gas generation after high-temperature storage;
[0060] (i) The rebound rate of the pole piece after 48 hours of rolling is 0.2%-1.2%, which is beneficial to improve the subsequent expansion of the battery cell and the low-temperature cold start performance of the battery.
[0061] In an optional embodiment, the preparation of the negative electrode plate described in the present application adopts a negative electrode hard carbon material, PVDF as a binder, and carbon black and carbon nanotubes as a conductive agent; the slurry is mixed and prepared according to the selected ratio and coated on the current collector aluminum foil. The current collector aluminum foil is subjected to corona treatment or coating treatment to facilitate the adhesion of the slurry.
[0062] In a second aspect, the present application provides a sodium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet; the negative electrode sheet is the negative electrode sheet described in the first aspect above.
[0063] In an optional embodiment, the positive electrode plate includes a positive electrode active material. As an exemplary embodiment, the positive electrode active material may optionally include one or more of a Prussian blue material, a transition metal layered oxide, and a polyanionic material. As an exemplary embodiment, the amount of the positive electrode active material added is 88wt%-96wt%, such as 88wt%, 89wt%, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, etc., or within the range of any two of the above values.
[0064] In an optional embodiment, the positive electrode plate is prepared by using a selected positive electrode active material, adding a binder, a conductive agent, etc., mixing and preparing a slurry according to a selected ratio, and coating it on a current collector aluminum foil. The current collector aluminum foil is treated with corona or a coating to facilitate the adhesion of the slurry.
[0065] In an optional embodiment, the binder in the positive electrode plate includes PVDF.
[0066] In an optional embodiment, the conductive agent in the positive electrode plate includes carbon black and / or carbon nanotubes.
[0067] In an optional embodiment, the density M of the electrolyte is 1.1 g / cm 3 -1.3g / cm 3 ;
[0068] In an optional embodiment, the conductivity ρ of the electrolyte is 8.5 ms / cm-9.5 ms / cm.
[0069] In an optional embodiment, the conductivity ρ of the electrolyte is related to the F content F in the negative electrode plate. wt% Satisfies the following relationship: 0.1g·ms / cm 4 ≤ρ×F wt% ≤0.5g·ms / cm 4 When the above relationship is met, the negative electrode active particles can maintain appropriate cohesion, so that there are appropriate gaps between the particles, which is conducive to the infiltration of the electrolyte, so that the negative electrode active layer will not cause powder loss during the cycle and can have a higher conductivity, which is conducive to ion conduction and reduces polarization, thereby reducing the low-temperature internal resistance of the battery and improving the low-temperature cold start performance and platform voltage of the battery.
[0070] In an optional embodiment, the electrolyte comprises an organic solvent system electrolyte. As an exemplary embodiment, the organic solvent is at least one selected from acetonitrile, tetrahydrofuran, ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, propyl propionate, ethyl propionate, propyl acetate, ethyl acetate, ethyl methyl carbonate or dimethyl sulfoxide.
[0071] In an alternative embodiment, the selected sodium salt is selected from NaPF 6 , NaBF 4 、NaClO 4 、NaAsF 6 and NaCF 3 SO 3 At least one of .
[0072] In an optional embodiment, the porosity of the separator is 40%-55%.
[0073] In an optional embodiment, the diaphragm includes a substrate and a polyethylene (PE) film, wherein the substrate thickness can be selected to be 5μm-12μm, and the film thickness can be selected to be 10μm-18μm; as an exemplary embodiment, a diaphragm with a surface coating of ceramic and polyvinylidene fluoride (PVDF) material can also be selected, and the preferred coating thickness is 2μm-4μm.
[0074] It will be understood by those skilled in the art that the sodium ion secondary battery includes a positive electrode, a negative electrode, a separator and an electrolyte. As an example, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer, the positive electrode collector having two surfaces opposite to each other in the thickness direction thereof, and the positive electrode active material layer is disposed on any one or both of the two surfaces opposite to the positive electrode collector. The materials, composition and manufacturing methods of the positive electrode plates used in the sodium ion secondary battery of the present application may include any technology disclosed in the prior art. As an example, the negative electrode plate includes a negative electrode collector and a negative electrode active material layer, the negative electrode collector having two surfaces opposite to each other in the thickness direction thereof, and the negative electrode active material layer is disposed on any one or both of the two surfaces opposite to the negative electrode collector. The materials, composition and manufacturing methods of the negative electrode plates used in the sodium ion secondary battery of the present application may include any technology disclosed in the prior art.
[0075] The electrolyte used in the sodium ion secondary battery of the present application may include any technology disclosed in the prior art.
[0076] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. In all examples and comparative examples of the present application, the unit wt% represents the mass percentage content.
[0077] Embodiment 1-21
[0078] The preparation method of the negative electrode sheet described in the following embodiment of the present application includes the following steps: using hard carbon as the negative electrode active material, adding a conductive agent (carbon nanotubes and / or carbon black) and a binder (PVDF) into a stirring tank, adding NMP, stirring thoroughly, passing through a 200-mesh sieve to prepare a negative electrode slurry, and then using a coating machine to coat the slurry on an aluminum foil, and rolling to obtain the desired negative electrode sheet.
[0079] In the negative electrode sheets described in the following Examples 1-21 of the present application, the parameter requirements and proportions of the selected negative electrode active material, conductive agent, and binder are shown in Table 1 below.
[0080] Table 1 Negative electrode sheet system of the embodiment
[0081]
[0082]
[0083] In the parameters in Table 1 above, D10 refers to the particle size corresponding to 10% of the cumulative volume percentage of the negative electrode active material, D99 refers to the particle size corresponding to 99% of the cumulative volume percentage of the negative electrode active material, and D50 refers to the particle size corresponding to 50% of the cumulative volume percentage of the negative electrode active material, that is, the median particle size of the volume distribution. The units of D10, D50, and D99 are all μm.
[0084] Comparative Examples 1-19
[0085] The following comparative example of the present application is prepared by referring to the example 1, the only difference being that the parameters for adjusting each component are different. The specific difference parameters are detailed in Table 2 below.
[0086] Table 2 Comparative negative electrode sheet system
[0087]
[0088] Application Example 1-21
[0089] The following application examples 1-21 of the present application respectively use the negative electrode sheets prepared in embodiments 1-21 to prepare the sodium ion battery.
[0090] Preparation of positive electrode sheet: Select sodium salt positive electrode active material, add conductive agent (acetylene black) and binder (polyvinylidene fluoride), add them into a stirring tank according to the selected ratio, add NMP solvent and stir thoroughly, pass through a 200-mesh sieve to form positive electrode slurry, and then use a coater to coat the slurry on aluminum foil and roll it to obtain a positive electrode sheet.
[0091] Preparation of positive electrode: Sodium layered oxide (Na[Ni 0.5 Fe0.5 ]O 2 ) is used as the positive electrode active material, and then added into a stirring tank with a conductive agent (acetylene black) and a binder (polyvinylidene fluoride) in a mass ratio of 93:5:2, and NMP solvent is added, and the mixture is fully stirred and passed through a 200-mesh sieve to form a positive electrode slurry. The slurry is then coated on an aluminum foil using a coating machine and rolled to obtain a positive electrode sheet.
[0092] Preparation of electrolyte: In a glove box filled with argon (H 2 O<0.1ppm, O 2 <0.1ppm), PC / DEC / PP were mixed evenly in a mass ratio of 30 / 40 / 30, and then 1 mol / L of fully dried sodium hexafluorophosphate (NaPF 6 ), after dissolving, add 12wt% of fluoroethylene carbonate, 2wt% of 1,3-propane sultone, and 2wt% of 1,3,6-hexanetrinitrile based on the total mass of the electrolyte, stir evenly, and after the moisture and free acid tests are qualified, the desired electrolyte is obtained.
[0093] Assembling the battery cell: laminating the negative electrode sheets prepared in the above embodiments 1-15 with the positive electrode sheets and polyethylene separators to form a stacked core, packaging it with aluminum-plastic film, baking to remove moisture, injecting the selected electrolyte, and forming the battery cell using a hot pressing process.
[0094] Comparative Application Example 1-19
[0095] The following comparative application examples of the present application are prepared by referring to the solutions in application examples 1-19, the only difference being that the negative electrode plates prepared in comparative examples 1-19 are respectively used.
[0096] Experimental example
[0097] 1. Performance of negative electrode
[0098] The negative electrode sheets prepared in the above-mentioned Examples 1-21 and Comparative Examples 1-19 were respectively taken to carry out corresponding performance tests.
[0099] Porosity: Cut the stacked negative electrode sheet according to the cutting board, and measure the cut sample to obtain the sample area A. Then measure the thickness of the sample, measure it 10 times, calculate the average value T, and calculate the apparent volume of the electrode V0 = A*T. Use an electronic balance to measure the weight of the negative electrode sheet, measure it 3 times, and get the average value M. Use a true density meter to test the true density ρ of the electrode sheet, and then calculate its true volume V1 = M / ρ; Calculate the porosity of the negative electrode sheet according to the following formula: Porosity C (%) = (V0-V1) / V0×100%. .
[0100] Peeling force: Cut a 100mm long and 24mm wide positive electrode current collector coated with the first coating as the sample to be tested; fix the positive electrode current collector on the upper and lower fixtures of the universal tensile machine; peel the sample 180°, the test speed is 100mm / min, and the test displacement distance is 80mm. The peeling force is obtained by converting the parameters measured by the tensile machine.
[0101] Surface resistance: Use a bulk resistance meter to test the coating surface resistance.
[0102] Distribution content of conductive agent: Under a scanning electron microscope, randomly select an area of 50 microns * 50 microns on the surface of the active layer, divide the image into 100 * 100 grids, calculate the ratio of the number of grids occupied by the conductive agent (when the area of the conductive agent in the grid exceeds half, it is regarded as occupying the grid) to the total number of grids, take 10 different positions for measurement and calculate the average value, which is the distribution content of the conductive agent.
[0103] In this experimental example, the performance test results of each negative electrode sheet are shown in Table 3 below.
[0104] Table 3 Negative electrode performance test results
[0105]
[0106]
[0107] In this experimental example, the SEM images of the electrode sheets prepared in Example 1 and Comparative Example 1 are shown in the attached Figure 1 As shown, it can be seen that the conductive agent in the electrode sheet in Example 1 is evenly distributed on the surface of the negative electrode particles, showing good dispersion performance; the conductive agent in the comparative example with the same ratio is unevenly distributed, with only a small amount of conductive agent on the surface of the particles, and it is speculated that there is more local agglomeration.
[0108] In this experimental example, the element distribution spectra of the electrode prepared in Example 1 and Comparative Example 1 are shown in the attached Figure 2 As shown. It can be seen that the EDS of the negative electrode prepared in Example 1 can clearly detect the F element content, and the proportion is relatively high; while the electrode prepared in Comparative Example 1 does not contain the F element.
[0109] 2. DQ / DV test performance
[0110] The sodium ion batteries prepared in the above application examples 1-21 and comparative application examples 1-19 were respectively taken for performance testing. Test method: The selected batteries were respectively left for 5 minutes, charged at a constant current of 0.1C for 63 minutes to 2.5V; then continued to be left for 5 minutes, charged at a constant current of 0.5C for 30 minutes to 3.9V; then left for 1 minute again, charged at a constant current and constant voltage of 0.7C to 3.9V; and continued to be left for 5 minutes.
[0111] In this experimental example, the test results of each battery are shown in Tables 4-5 below.
[0112] Table 4 DQ / QV peak position of full battery for the first charge
[0113]
[0114]
[0115]
[0116] Table 5 Full battery charge and discharge DQ / QV peak position
[0117]
[0118]
[0119] In this experimental example, the DQ / DV curves of the first charge of the sodium ion battery in Application Example 1 and Comparative Application Example 1 are shown in the attached Figure 3 As shown, it can be seen that the product prepared in Application Example 1 undergoes film formation reaction earlier, with more sodium adsorption and embedding in the low voltage stage, and a lower peak position in the subsequent reaction; in contrast, the reaction in the film formation stage is slower, and the peak position in the subsequent reaction is higher. This also shows that the negative electrode sheet and sodium ion battery prepared in this application have higher kinetic performance, smaller polarization, and more complete and dense film formation, which is beneficial to subsequent rate, low-temperature discharge, cycle and storage.
[0120] In this experimental example, the ICA curves of single charge and discharge of the sodium ion battery in Application Example 1 and Comparative Application Example 1 are shown in the attached Figure 4 As shown, it can be seen that the product prepared in Application Example 1 has a lower reaction peak in the 2.6-3.0V range; the comparison group has a higher peak in this range.
[0121] In this experimental example, the dQ / dV cycle curve of the sodium ion battery cycle process in Application Example 1 is shown in the attached figure. Figure 5 As shown, it can be seen that as the cycle progresses, the polarization gradually increases, which is manifested as a shift in the potential of peak 1; at the same time, the corresponding peak 2 decreases, indicating that the loss of active substances gradually increases.
[0122] It can be seen that the dQ / dV curve of the sodium ion battery system described in the present application has a lower peak value, and the corresponding peak position of SEI film formation is lower, and the experimental group is conducive to the formation of a thinner film layer; the charge and discharge oxidation peak and reduction peak values are lower, which is beneficial to smaller electrochemical polarization and is conducive to reducing the overall polarization.
[0123] 3. Sodium ion battery performance
[0124] The sodium ion batteries prepared in the above-mentioned application examples 1-21 and comparative application examples 1-19 were respectively taken for corresponding performance tests.
[0125] Cyclic test method: (1) At 25±2℃, charge at 1C constant current and constant voltage to an upper limit voltage of 3.9V, with a cut-off current of 0.05C, and leave for 10 minutes; (2) discharge at 1C constant current to 2.0V, and leave for 10 minutes; (3) repeat steps 1 to 2 until 2000 cycles are reached.
[0126] Cold start test method: (1) At 25±2℃, charge at 0.2C constant current and constant voltage to an upper limit voltage of 3.9V, cutoff current of 0.05C, and leave for 10 minutes; (2) Discharge at 0.2C constant current to 2.0V, and leave for 10 minutes; (3) Charge at 0.2C constant current and constant voltage to an upper limit voltage of 3.9V, cutoff current of 0.05C, and leave for 10 minutes; (4) Discharge at 0.2C to 50% SOC, and leave for 10 minutes; (5) Place the battery cell in a -28℃ constant temperature box and leave for 4 hours; (6) Discharge at 3C for 2s, then at 15C for 0.5s, and then at 11.5C for 10s; (7) Record the lowest voltage after each discharge step as the cold start voltage.
[0127] Float charge test method: (1) At 45±2℃, charge and discharge once at 1C and record the initial capacity; leave for 30 minutes; (2) Charge at 1C constant current to 3.9V and then charge at constant voltage, with a cut-off of 0.05C; (3) Charge at 3.9V constant voltage until it reaches 180D.
[0128] 60℃ high temperature storage test method: (1) In a 25±2℃ environment, charge and discharge once at 1C to record the initial capacity; leave for 30 minutes; (2) Charge to 3.9V at 1C constant current and constant voltage, and cut off at 0.05C; place the battery cell in a 60±2℃ constant temperature box until it reaches 180 days; (3) Test the battery cell capacity retention rate and recovery rate by discharging and charging at 1C.
[0129] Capacity percentage above 25℃ platform voltage: The cell is fully charged at 25±2℃ at 0.2C constant current and constant voltage, and cut off at 0.05C; then discharged at 0.2C to the lower limit voltage, and the initial capacity C0 is tested. The platform voltage is the ratio of discharge energy to discharge capacity. The capacity C1 corresponding to the platform voltage is found from the discharge capacity and voltage data. The capacity percentage above the platform voltage is C1 / C0×100%.
[0130] The test methods for other temperatures of -30℃, -20℃, 45℃ and 60℃ refer to the capacity percentage method above the 25℃ platform voltage mentioned above.
[0131] 25℃ 10C rate discharge: Charge and discharge the battery at 25±2℃ at 0.2C to test the initial capacity, then fully charge at 0.2C constant current and constant voltage, and cut off at 0.05C; then discharge at 10C current rate to the lower limit voltage. The rate discharge capacity ratio is the ratio of 10C rate discharge capacity to 0.2C initial capacity.
[0132] 0℃50%SOC DCR test: fully charge the battery cell at room temperature with 1C constant current and constant voltage, then let it stand at 0℃ for 4h, and discharge at 0.2C to test the initial capacity; then let it stand at room temperature for 2h, fully charge at 1C constant current and constant voltage; then let it stand at 0℃ for 4h, then discharge at 0.2C constant current to 50%SOC, let it stand for 2h, record the terminal voltage, then discharge at 3C for 10s, and record the discharge end voltage; The DCR value is the ratio of voltage change to current.
[0133] 2000T cycle 50% SOC DCR: The battery cell that has been cycled for 2000T is fully charged at 1C constant current and constant voltage at room temperature, and discharged at 0.2C to test the initial capacity; then fully charged at 1C constant current and constant voltage, discharged at 0.2C constant current to 50% SOC, stood for 2h, recorded the terminal voltage, then discharged at 3C for 10s, and recorded the discharge terminal voltage; The DCR value is the ratio of voltage change to current.
[0134] In this experimental example, the test results of each sodium ion battery are shown in Tables 6-8 below.
[0135] Table 6 Sodium ion battery performance results
[0136]
[0137]
[0138]
[0139] Table 7 Sodium ion battery performance test results
[0140]
[0141]
[0142] Table 8 Sodium ion battery performance results
[0143]
[0144]
[0145] It can be seen from the above results that the sodium ion battery prepared with the negative electrode plate described in the present application can effectively improve the low-temperature (-25°C) cold start performance of the entire system; and improve the platform voltage of the system at different temperatures. The sodium ion battery described in the present application effectively reduces the DCR, while effectively improving the cycle capacity retention rate, and reducing the DCR growth after the cycle; it not only improves the proportion of charging capacity above the platform voltage under low and high temperature conditions, but also improves the proportion of rate discharge capacity of the battery cell, reducing the DCR of the battery cell and the DCR after the cycle. The sodium ion battery described in the present application also improves the floating charge performance of the system, and the 180D floating charge does not produce gas; and improves the high-temperature storage capacity retention rate and expansion rate of the battery cell, and does not produce gas during storage.
[0146] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector; The negative electrode active layer contains F element and C element, wherein: The mass content of the F element based on the total amount of the negative electrode active layer wt% Satisfies: 0wt%<F wt% ≤7.6wt%; The mass content of F element F wt% and the mass content of the C element C wt% Satisfies the following relationship: 0%<F wt% / C wt% ×100%≤8.44%.
2. The negative electrode plate according to claim 1, characterized in that: The mass content of the F element based on the total amount of the negative electrode active layer wt% Satisfy: 0.2wt%<F wt% ≤3wt%; and / or, The mass content of F element F wt% and the mass content of the C element C wt% Satisfy the following relationship: 0.2%<F wt% / C wt% ×100%≤3%; and / or, The negative electrode active layer includes a conductive agent.
3. The negative electrode plate according to claim 2, characterized in that: The distribution content of the conductive agent on the surface of the negative electrode active layer is 20%-35%; and / or, The conductive agent includes at least one of carbon nanotubes, carbon black, conductive graphite, graphene or carbon fiber; preferably, the conductive agent includes at least carbon nanotubes and / or carbon black; Preferably, the conductive agent includes a mixture of carbon nanotubes and / or carbon black, and at least one selected from the conductive graphite, graphene or carbon fiber.
4. The negative electrode plate according to claim 3, characterized in that: In the negative electrode active layer, the mass content of the F element is F wt% The aspect ratio d of the carbon nanotube satisfies the following relationship: 0<F wt% ×d≤380; and / or, The aspect ratio d of the carbon nanotubes satisfies the following relationship: 300≤d≤5000; and / or, The diameter of the carbon nanotube is 5nm-15nm; and / or, The specific surface area of the carbon nanotubes is 150 m 2 / g-350m 2 / g; and / or, The primary particle size of the carbon black is 18nm-35nm; and / or, The specific surface area of the carbon black is 120 m 2 / g-180m 2 / g; and / or, The oil absorption value of the carbon black is 150ml / 100g-180ml / 100g; and / or, The mass ratio of the carbon nanotubes to the carbon black is 1:3-1:
6.
5. The negative electrode sheet according to claim 1 or 2, characterized in that: The negative electrode active layer comprises a negative electrode active material, wherein the negative electrode active material comprises hard carbon; and / or, The negative electrode active layer includes a binder, and the binder includes a fluorine-containing binder.
6. The negative electrode plate according to claim 5, characterized in that: The hard carbon includes hard carbon with irregular angular structure; And / or, the water content of the hard carbon is ≤300ppm; And / or, the binder includes PVDF.
7. The negative electrode sheet according to claim 1 or 2, characterized in that: The negative electrode active layer comprises a negative electrode active material, a binder and a conductive agent; wherein, Based on a total amount of 100 wt%, the mass ratio of the negative electrode active material, the binder and the conductive agent is 88 wt%-96 wt%: 0.34 wt%-10 wt%: 1 wt%-8 wt%.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The negative electrode plate has at least one of the following features (a)-(e): (a) The initial efficiency of the negative electrode meets 85%-95%; (b) The electrode sheet surface resistance meets 1mΩ-4mΩ; (c) The electrode resistivity meets 0.001Ω·m-0.01Ω·m; (d) The average peeling force of the electrode meets the requirements of 0.24N-3.5N; (e) The porosity of the electrode should be between 45% and 55%; Preferably, the negative electrode plate also has at least one of the following features (f)-(i): (f) The gram capacity of the negative electrode meets 280 mAh / g-330 mAh / g; (g) The water content of the electrode after baking before injection meets 100ppm-400ppm; (h) The compaction density of the pole piece meets 0.8g / cm 3 -1.5g / cm 3 ; (i) The rebound rate of the pole piece after 48 hours of rolling is 0.2%-1.2%.
9. A sodium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet; characterized in that: The negative electrode plate is the negative electrode plate according to any one of claims 1 to 8.
10. The sodium ion secondary battery according to claim 9, characterized in that: The positive electrode plate comprises a positive electrode active material, wherein the positive electrode active material comprises one or more of a Prussian blue material, a transition metal layered oxide and a polyanion material; and / or, The density M of the electrolyte is 1.1 g / cm 3 -1.3g / cm 3 and / or, The conductivity ρ of the electrolyte is 8.5 ms / cm-9.5 ms / cm; and / or, The conductivity ρ of the electrolyte is related to the F content F in the negative electrode plate. wt% Satisfies the following relationship: 0.1ms / cm≤ρ×F wt% ≤0.5ms / cm; and / or, The porosity of the separator is 40%-55%.